A Study on the Potential of Vitamin D in the Prophylactic, Therapeutic and Recovery of Cardiovascular Diseases - Gana Sahas S, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
in the blood lead to increased cardiovascular disease (CVD) occurrences but experimental treatment results remain uncertain. We examined whether vitamin D sufficiency is associated with reduced new-onset CVD, attenuated disease progression and enhanced post-event recovery. Methods: The study analyzed 4 218 adults with 63 ± 11-year mean age and 43 percent female participation who were CVD-free at baseline through three serum 25(OH)D groups. The research period extended up to 8 years with a median duration of 6.1 years. The study followed participants to assess MACE incidents including MI, stroke, and CV death along with other secondary targets. Other secondary goals covered changes in cIMT, SBP, and hs-CRP besides functional recovery assessment through 6MWD post-acute MI. The study utilized both Multivariable Cox and mixed-effects models for analysis while adjusting for the demographic as well as the clinical and behavioural confounders.. Results: The research showed that MACE risk decreased by 23 % for patients with vitamin D sufficiency compared to those with deficiency (adjusted HR 0.77, 95 %CI 0.63-0.93; p = 0.006). Subjects with sufficient vitamin D levels demonstrated slower annualised cIMT progression rates at -0.014 mm/y and their SBP decreased by -4.3 mmHg (p = 0.02 and p = 0.01). Additionally hs-CRP levels dropped 18% (p < 0.001). The pre-event 25(OH)D level of a sufficient range for 412 incident MI survivors led to 29 meters increase in 3-month 6MWD distance and 17 percent fewer hospital readmissions at year one (p = 0.03). Conclusion: Vitamin D sufficiency was independently associated with lower CVD incidence, slower subclinical atherosclerosis, favourable haemodynamic and inflammatory profiles, and better early functional recovery after MI. Although residual confounding cannot be excluded, these findings support prospective trials targeting personalised vitamin D optimisation in cardiovascular prevention and rehabilitation.